Let z=f(x+cy) be the trial solution of the given PDE
Let us take u= x+cy, so z=f(u)
Then we have p=dz/du, q=cdz/du
q/p=c
q=pc
p+p2c2=0 p(1+pc2)=0
1+pc2=0
p=-1/c2
dz=pdx+qdy=p(dx+cdy)=0
dx+cdy=0
dx=-cdy
x=-cy+c1
Substituting the value of p
p, we get
"dz=\\frac{-(dx+cdy)}{c^2}" =0
z=-x/c2-y/c+c1
3s=-s/c+c1
s/c=c1-3s
c=s(c1-3s)
c1=3s+s/c
0=-cs+3s+s/c
0=-c2s+3cs+s
D=9s2 +4s
"c=\\frac{-3s+\\sqrt{9s^2+4s}}{-2}"
Answer: "\\frac{4}{(-3s+\\sqrt{9s^2+4s})^2}-(\\frac{2}{(-3s+\\sqrt{9s^2+4s})})^2=0"
Comments
Leave a comment